The UK referendum: And the future of the European Project - Guy De Jonquières (European Centre for International Political Economy (ECIPE), 2016)
It is on the pocketbook issues that Britain's Remain campaign has chosen to take its stand. For weeks, it has bombarded the public with warnings and research purporting to show that Brexit would take a toll on economic growth, living standards, public services and even property prices. International institutions such as the International Monetary Fund, the Organisation for Economic Cooperation and Development and the World Bank, along with government leaders around the world, have chimed in with statements that Britain would be worse off outside the EU. It is still unclear how far such arguments will sway the undecided voters who will determine that outcome of the referendum, in the face of Leave's focus on the more emotive issue of curbing immigration. It is also indicative of the difficulty of arguing a positive case for staying in the EU that so few in the Remain campaign try very hard to make it. Furthermore, Remain needs to overcome wider public disaffection with and mistrust of, not just EU institutions, but establishment politics at national level as well. A similar popular mood is spreading across much of the rest of Europe. A UK vote for Brexit would strengthen the growing populist and nationalist forces in the EU that want their countries to leave it and even to dismantle the European Project altogether. What makes that challenge so powerful is that Europe's leaders, under rising pressure from insurgent parties at home, have few ideas about how to respond to them. There are fundamental problems at the heart of the European Project. But there is a serious shortage of realistic solutions, still less a political consensus on what they should be.
Keywords: 330; EU-Mitgliedschaft; Exit-Strategie; Großbritannien